Probabilistic-based structural safety analysis of concrete gravity dams - Pereira, Renato Miguel Rodrigues (2019)
The construction and operation of dams, associated with the use of water resources, aims generically at water supplying, the energy producing and, in many cases, flow regulating and flood controlling. Considering the dam dimensions and the potential risks associated with its structural failure, due to the occupation of the downstream valley, and to the costs of the construction, maintenance and rehabilitation, the use of probabilistic principles in its design, as it is already performed for other type of structures, is justified considering adequate levels of safety. The objections shared throughout the dam engineering community, regarding the difficulty in estimating the probability of failure for concrete dams, are expectedly overcome by the failure mode and uncertainty modeling, allowing the application of probabilistic principles for their safety analysis, based on conservative simplifications regarding the structural behavior, namely: (i) the definition of the failure surface (dam-foundation interface); (ii) the consideration of rigid body failure mechanisms; and (iii) the consideration of the residual shear strength, given only by the frictional component, corresponding to a limit analysis valid for ultimate limit states. For that purpose, the failure modes are derived from the current construction and design practice by comparing analytical and numerical models of a generic, though representative, case study. The uncertainties involved in the safety of concrete dams are statistically quantified, through the definition of probabilistic distributions for loads and material properties, using, in addition to the elements found in the literature, the information available at LNEC about those features, resulting from the monitoring of the concrete dam behavior during the construction, first filling and operation periods. This work explores the required tasks for the adoption of the partial safety factor method for the safety analysis of concrete gravity dams, at the design phase. Two representative studies regarding the reliability-based design of concrete gravity dams and partial safety factor calibration are presented, intending to stimulate the discussion on the applicability of probabilistic principles for the design of concrete dams, as well as, to influence the safety criteria to be considered in a future revision of the dam safety regulation. The obtained results confirm that the seismic load combination and the sliding failure modes are the most conditioning situations. It is also observed that cross-sections profiles flatter than currently used may be needed for high intensity seismic zones. Partial safety factors that approximate reasonably the reliability-based results could be derived.